2009
DOI: 10.1007/s11071-009-9551-7
|View full text |Cite
|
Sign up to set email alerts
|

Analytical study of nonlinear synchronous full annular rub motion of flexible rotor–stator system and its dynamic stability

Abstract: The nonlinear synchronous full annular rub motion of a flexible rotor induced by the mass unbalance and the contact-rub force with rigid and flexible stator is studied analytically. The nonlinear property is due to the dry friction force between stator and rotor. The exact solutions of the synchronous full annular rub motion and its run speed regions are obtained. The stability of the synchronous full annular rub motion is discussed analytically. The stability criterion and the stability regions of the synchro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…x The local contact stiffness coefficient can be determined by the equivalent stiffness of the contact linear spring force model [20],…”
Section: Test Using the Simulated Rubbing Signalmentioning
confidence: 99%
“…x The local contact stiffness coefficient can be determined by the equivalent stiffness of the contact linear spring force model [20],…”
Section: Test Using the Simulated Rubbing Signalmentioning
confidence: 99%
“…From the whirl frequency of the dry friction backward whirl, w , it is more easily found that the whirl frequencies increase with the rotation speed and have different ranges of values in the two existence regions when μ = 0.25. Actually, the magnitudes of the whirl frequencies in the two existence regions are limited respectively by the two natural frequencies of the coupled rotor-casing/foundation system with zero clearance as given by (3).…”
Section: The Backward Full Annular Rubmentioning
confidence: 99%
“…In this aspect three simplified rotor/stator models were studied. The first rotor/stator model consists of a Jeffcott rotor and a rigid stator that is rigidly fixed on a rigid foundation [1][2][3]. The second rotor/stator model still uses a Jeffcott rotor but the stator is modeled as an added stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…(8) and (9). For physical systems only stable solutions are of interest because they reflect the system response which can really occur.…”
Section: Stability Of Synchronous Full Annular Rubmentioning
confidence: 99%
“…The response and stability for both two cases were obtained, and the effect of parameters, such as mass unbalance, dry friction, rotor damping, and seal stiffness, on shifting from synchronous response to reverse rub were discussed. Zhang et al [9][10][11] studied the SFARM (synchronous full annular rub motion) of a single disk rotor and a flexible rotor, respectively. Perturbation method was employed to solve the exact solution and its stability regions.…”
Section: Introductionmentioning
confidence: 99%